A Dual Half-Active Bridge Resonant Converter for Solar PV Integration Using Grey Wolf Optimization - Barnawal P.J.; Lal V.N.; Singh R.K. (My University, 2025)
This paper proposes a dual half-active bridge resonant converter for solar photovoltaic integration. In solar PV applications, traditional algorithms often struggle to harness maximum power under partial shading conditions, resulting in the underutilization of solar energy. Additionally, electrolytic capacitors used for voltage smoothening suffer from aging effects leading to an unreliable operation of the power converters. If these capacitors are employed for solar PV applications, they may need to be replaced several times over the lifespan of solar panels. To resolve these concerns an isolated dual half-active bridge resonant converter is proposed and integrated with the solar panel using a grey wolf optimization-based power tracking algorithm. The structure of the proposed converter is embedded with reliable film capacitors to eliminate the need for electrolytic filter capacitors for voltage smoothening, making the converter simple, reliable, and easy to control. The proposed converter is analyzed and soft-switching conditions are formulated using a modified fundamental harmonics approximation. The feasibility of using film capacitors is verified using the dynamic changes in load. PV curves of different ratings are formed using a solar PV emulator (Chroma 62100H-600S) and maximum power is efficiently drawn under uniform irradiance and partial shading conditions using a 500 W laboratory-built prototype. © 2024 IEEE.